Topological stability of the averagings of functions - Maksimenko, S. I.; Marunkevych, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We present sufficient conditions for the topological stability of the averagings of piecewise smooth functions f : R → R with finitely many extrema with respect to discrete measures with finite supports.